KEHIDUPAN SOSIAL EKONOMI WANITA PENGRAJIN SONGKET DI KECAMATAN SILUNGKANG KOTA SAWAHLUNTO TAHUN (2000 â 2012) - AFRINENGSIH, REFI - (Pendidikan Sejarah, 2014)
This thesis examines the social and economic life of women artisans in songket Silungkang city districts Sawahlunto years (2000-2012). This study aims to: (1) describe the Women artisans in songket Silungkang years 2000 to 2012 (2) describe the impact of working as a craftsman on the function of women in the household in 2000 to 2012 (3) describe the impact of working women to the household economy from 2000 to in 2012. This research includes the study of history. Therefore, this study follows the methods of historical research with the following procedures: (1) Heuristic is to look for and collect information obtained from primary sources and secondary sources (2) the source of criticism by testing for the authenticity and validity of information (3) Interpretation interpreting and connecting existing facts (4) Presentation of research results (historiography). The results showed that the cause of women Silungkang worked as a craftsman is to cover the needs of the economy where the main livelihood as traders and farmers no longer meets the needs of the family. It is also driven by geography and customs in Silungkang which does not allow to look for another job, so from time to time to see an increase in the number of artisans Silungkang songket. The results of this study also showed that the operation of women in households that women have ignored his work as a housewife. As a woman in Silungkang craftsmen work harder to earn better income. They also strive to improve the quality of songket weaving so the results are Fab. These efforts they do to get better results and a good sale price. With revenue received per day or per week, most women in Silungkang have helped their husbands earn a living, buy home appliances and finance the childrens education. This songket weaving craft has contributed to support the domestic life of women in Silungkang.